2014
DOI: 10.1155/2014/152010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rat Medicated Serum Containing You Gui Wan on Mouse Oocyte In Vitro Maturation and Subsequent Fertilization Competence

Abstract: You Gui Wan (YGW) is a classic herbal formula in traditional Chinese medicine (TCM) used for the clinical treatment of infertility. This study was to explore whether YGW has an impact on mouse oocyte maturation in vitro and subsequent fertilization competence. Rat medicated serum containing YGW was prepared by orally administrating YGW. Mouse immature oocytes were cultured with YGW medicated serum and compared to those cultured with or without normal rat serum or follicle-stimulating hormone (FSH). YGW medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…From this point of view, germ cells may correspond to the congenital essence found in TCM theories [ 8 ], and the actions of herbal formulas that reinforce the Ying or Yang deficiency may be presumed to influence germ cell fertilization abilities as well as the formation and/or differentiation of germ cells. This hypothesis has been supported by our recent studies which demonstrate that YGW decoctions can enhance the fertilizing abilities of mouse sperm in vivo and in vitro [ 9 ] and that rat medicated serums containing YGW can increase mouse oocytes in vitro maturation and subsequent in vitro fertilization abilities [ 10 ].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…From this point of view, germ cells may correspond to the congenital essence found in TCM theories [ 8 ], and the actions of herbal formulas that reinforce the Ying or Yang deficiency may be presumed to influence germ cell fertilization abilities as well as the formation and/or differentiation of germ cells. This hypothesis has been supported by our recent studies which demonstrate that YGW decoctions can enhance the fertilizing abilities of mouse sperm in vivo and in vitro [ 9 ] and that rat medicated serums containing YGW can increase mouse oocytes in vitro maturation and subsequent in vitro fertilization abilities [ 10 ].…”
Section: Introductionmentioning
confidence: 69%
“…Moreover, one of our recent studies showed that rat medicated serums containing YGW had a significant effect on mouse oocyte maturation in vitro via molecular signal pathways similar to those induced by FSH [ 10 ]. The results suggest that some active or biotransformed herbal ingredients in the medicated serums may have gonadotrophin functions to stimulate the production of estradiol from differentiated granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sera from the treated rats were prepared according to the previous protocols [17]. Briefly, 24 Sprague Dawley rats, aged between 6 and 8 weeks old and weighing between 180 and 220 g, were divided into 4 groups, with 6 rats in each group: normal control (NC) group, low dose of Liuweibuqi (LWBQ low) group, mid dose of Liuweibuqi (LWBQ mid) group and high dose of Liuweibuqi (LWBQ high) group.…”
Section: Methodsmentioning
confidence: 99%
“…BMECs were isolated as previously described. 18) Briefly, mouse cerebral cortex was isolated and digested in 0.25% trypsin at 37°C for 30 min and centrifuged. The second band containing micro-vessels was collected and plated onto collagen-coated dishes.…”
Section: Methodsmentioning
confidence: 99%